Clinical efficacy of different dosage forms containing vitamin D: design and study outcomes of a randomized, comparative clinical trial - Sapkal, Nidhi; Chhaya, Gaurav; Satya, Milan; Shah, Dhara (International Journal of Clinical Trials, 2020)
Background: Different dosage forms of vitamin D like tablets, soft gelatin capsules, oral granules, powders, solutions and thin films are available. The objective of the present study was to evaluate and compare the clinical efficacy of three different dosage forms of vitamin D3 namely, orally disintegrating strips, oral granules and oral solution. Methods: An open label, single centre, prospective, randomized, parallel group, comparative study was conducted for a period of 4 months. The study participants were divided into three groups (A, B, C) and received the respective treatments (orally disintegrating strips, n=20; granules, n=20; oral nano solution, n=10) for the study period. The estimation of blood levels of 25-hydroxy vitamin D [25(OH)D3] in all the subjects at day 0, 60 and 120 was carried out. Results: The normalization level of 25(OH)D3 achieved by the subjects in group A, group B and group C was 100%, 83.3% and 90% respectively after 90 days. Comparison of 25(OH)D3 level in all three groups showed significant increase at day 60. The levels were maintained at day 90 and 120 even after drastic reduction in dosage in Group A and group C. On day 120, the dose reduction was in the order of group A>group C>group B. Conclusions: All the three formulations showed increase in the level of 25(OH)D3. It can be concluded that oral disintegrating strips of 25(OH)D3 are clinically more efficient than other conventional dosage forms.